2015
DOI: 10.1186/s13167-015-0035-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of beneficial bacteria wall elasticity in regulating innate immune response

Abstract: BackgroundProbiotics have great potential to contribute to development of healthy dietary regimes, preventive care, and an integrated approach to immunity-related disease management. The bacterial wall is a dynamic entity, depending on many components and playing an essential role in modulating immune response. The impact of cell wall elasticity on the beneficial effects of probiotic strains has not been sufficiently studied.The aim was to investigate the effect of lactic acid bacteria (LAB) and bifidobacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…Healthy diet and nutrition are the very focus of the European Association for Predictive, Preventive and Personalised Medicine (EPMA), the main promoter of predictive, preventive, and personalized medicine (PPPM), and belong to the prioritized medical fields for long-term strategy of created multidisciplinary platform for progressing from “disease care” to “health care”: “advancing participatory medicine”, “well-being” concepts, and integrated approach. A major target of this approach is the effective management of immunity-related disorders, such as inflammation, atopy, asthma, musculoskeletal disorders, liver fibrosis, diabetes mellitus type 2 (T2D), metabolic syndrome, cardiovascular diseases (CVD), neurodegenerative diseases (NDD), atherosclerosis, and cancer [ 1 4 ].…”
Section: Reviewmentioning
confidence: 99%
“…Healthy diet and nutrition are the very focus of the European Association for Predictive, Preventive and Personalised Medicine (EPMA), the main promoter of predictive, preventive, and personalized medicine (PPPM), and belong to the prioritized medical fields for long-term strategy of created multidisciplinary platform for progressing from “disease care” to “health care”: “advancing participatory medicine”, “well-being” concepts, and integrated approach. A major target of this approach is the effective management of immunity-related disorders, such as inflammation, atopy, asthma, musculoskeletal disorders, liver fibrosis, diabetes mellitus type 2 (T2D), metabolic syndrome, cardiovascular diseases (CVD), neurodegenerative diseases (NDD), atherosclerosis, and cancer [ 1 4 ].…”
Section: Reviewmentioning
confidence: 99%
“…In addition, these strains of lactobacilli are characterized by specific immunomodulatory properties studied earlier in experiments on mice of the BALB / C line [3] and synergistic properties [6]. In similar studies, we have shown the ability of probiotic microorganisms to stimulate the local immune response and mechanisms that provide it [15,19].…”
Section: Methodsmentioning
confidence: 59%
“…According to classical views [13,19], functional foods include food and beverages whose use leads to regulation of a number of physiological processes of the human body to prevent the emergence of human diseases including (partially) caused by ISSN 1996-4536 immune-metabolic disorders of the body. Modern studies of human microbiota and its functional properties (so-called function) open up today the possibilities for constructing a new generation of FFPs [24].…”
Section: Introductionmentioning
confidence: 99%
“…However, more effective activator of cytokine production (IFN-γ and IL-12) in vitro among LAB strains appeared strains with more rigid cell wall. It is proved that L. acidophilus IMV B-7279, L. casei IMV B-7280, B. animalis VKL and B. animalis VKB is biocompatible, which allows to combine these strains of LAB and bifidobacteria with different degrees of the cell wall rigidity in different composition, thereby getting probiotic preparation with specified properties [20].…”
Section: Imunobiotics Are the Novel Biotech Drugs With Antibacterial mentioning
confidence: 99%